(3gOGjI GdbQBf Mhd GdMbGFb GdYdejI GdeJUdI HGdfHGJ ai GdbQBf GdcQje (B: s (3OQGSI JWHjbjI (B/ s - (3YeGO eMeO GdSjO Ydi eLGgOs; (3ShSf eMehO CHhWGdH (B: s; (3eMeO EHQGgje TQja (B: s ((3GdbGgQI (B: s (3YeGO eMeO GdSjO Ydi eLGgO (B: s, 2015)
(3JOhQ GdQSGdI Mhd EHQGR CgejI CHMGK GdEYLGR GdYdei hKeGQgG GdJi JXgQ ef NdGd (B: (3JfTjW GdeSdejf ddEcJTGaGJ GdchfjI (B: (3HOGaY ef GdMhGaR GdEjeGfjI (B.(3HGJ GdEYLGR GdYdei gPg GdCjGe ef Cbhi GdhSGFd ai GdOYhI Edi Gddg YR hLd (B: (3agh dZI GdYUQ (B: (3dZI GdYde GdPj jageg gDdGA ef ZjQ GdYQH (B. (3hHjGf hLg GdEYLGR GdbQBfi ddfHGJ aj GdbQBf hYOe JYGQV GdMbjbI GdYdejI eY GdMbjbI GdbQBfjI hJhVjM QDjI YdejI dYdeGA GdOjf GdESdGei hGdOYGI ddJaSjQGJ GdYdejI ai eLGd Yde GdfHGJ dCffG fSeY ef HYVge JaSjQGJ eLGajI JeGekG ddMbGFb GdYdejI hefGbVI ddMbGFb GdbQBfjI (B: (3MjK ffbd dge age dZI GdYUQ hdZI GdYde ai Yde GdfHGJ (B. (3heMGhdI JHSjW GdeYdheGJ GdYdejI dOi GdOGYjI GdESdGei hGdHYO Yf cKjQ ef GdJaUjdGJ hGdYedjGJ GdJi JMJGL ef ZjQ GdeJNUU Edi NdajI JYdjejI (B: (3hcja cGfJ gOGjI GdbQBf ai GdfHGJ hEYLGRg GdYdej ai GdYUQ GdMOjK s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQ GdYdhe (B- (3bSe GdTQjYI GdESdGejIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdMbjbI GdYdejIs; (3GdMbjbI GdbQBfjIs; (3GdfHGJs